MENTAL AND PSYCHOMOTOR RETARDATION IN EARLY CHILDHOOD: Overview and development of a protocol for neuropsychological assessment. - María del Mar Sánchez-Joya; Lola Roldán-Tapia; Lourdes Martinez; Rosa Canovas (CAEN, 2010)
Introduction: The last decades have brought great advances in the understanding of child neurodevelopment and knowledge of cognitive processes that occur in the brain from an early age. As a result and thanks to the large number of standardized and scientifically guaranteed neuropsychological tests that are available today, we can assess and diagnose with high specificity, deficits or delays in the acquisition of cognitive functions. Besides, it allows knowing the strengths or normality points of children with various pathologies. Objective: To present the concepts and a neuropsychological assessment protocol for mental retardation, pervasive developmental disorder and psychomotor retardation. Development: First, the authors present a general model of neuropsychological assessment in childhood. Second, he concept, classification and aetiology of mental retardation is revised and it is proposed a neuropsychological profile. Finally, the paradigms of pervasive developmental disorder and psychomotor retardation are shown. Conclusion: Based on standardized and validated test for child neuropsychological assessment, children cognitive disorders can be accurately identified to plan each child's cognitive stimulation, and thus optimize the results of the therapy.